Claire Davison, Béatrice Laurent, Caroline Patey, Natalie Vanfasse (eds.) Provence and the British Imagination (Altre Modernità, 2014)
Claire Davison, Béatrice Laurent,Caroline Patey, Natalie Vanfasse (eds.)Provence and the British Imagination(Milano, Ledizioni, 2013, 235 pp. ISBN 978-886-705-137-3)di Paolo Caponi